Measurement of CP asymmetries in D+(s) → ηπ+ and D+(s) → η′π+ decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2023)
Searches for CP violation in the decays D-(s)(+) -> eta pi(+) and D-(s)(+) -> eta'pi(+) are performed using pp collision data corresponding to 6 fb(-1) of integrated luminosity collected by the LHCb experiment. The calibration channels D-(s)(+) -> phi pi(+) are used to remove production and detection asymmetries. The resulting CP-violating asymmetries are A(CP) (D+ -> eta pi(+)) = (0.34 +/- 0.66 +/- 0.16 +/- 0.05)%, A(CP) (D-s(+) -> eta pi(+)) = (0.32 +/- 0.51 +/- 0.12)%, A(CP) (D+ -> eta'pi(+)) = (0.49 +/- 0.18 +/- 0.06 +/- 0.05)%, A(CP) (D-s(+) -> eta'pi(+)) = (0.01 +/- 0.12 +/- 0.08)%, where the first uncertainty is statistical, the second is systematic and the third, relevant for the D+ channels, is due to the uncertainty on A(CP) (D+ -> phi pi(+)). These measurements, currently the most precise for three of the four channels considered, are consistent with the absence of CP violation. A combination of these results with previous LHCb measurements is presented.